Code-switching in Language Classrooms: A Comparative Study of University Teachers’ Beliefs - Shaista Shehzadi (University of Chitral Journal of Linguistics and Literature, 2022)
The subject of first language (L1) usage or code-switching in relation to L2 (second language) education and learning has been a source of contention in the field of second language acquisition for decades. The assumption that first language (L1) must be used for second language (L2) education and learning has thus been supported by a number of studies, while some other works have provided evidence of the drawbacks of that L1 implementation. As of now, it is widely acknowledged that the idea of "belief" is a key factor influencing second language (L2) education and understanding. The current investigation compares the beliefs of various university teachers and instructors about the use of L1 in language classrooms in two different universities of two main cities, namely The University of Lahore and the National University of Modern Language in Lahore and Multan, respectively. In this research, it has been examined whether or not Multan and Lahore EFL lecturers have similar or divergent views on the use of L1 in their language courses. A questionnaire based on teachers’ beliefs was used to collect the data. Twenty EFL teachers from both settings were involved in the study. The research found that the opinions of two EFL teachers regarding the use of L1 for their approach to their subject of classroom management and CS for interpersonal connections were significantly different from one another.